Investigations of granular material behaviors using coupled Eulerian-Lagrangian technique: From granular collapse to fluid-structure interaction. (May 2020) - Lin, Cheng-Han; Hung, Ching; Hsu, Tsai-Yun
Abstract: In this study, a coupled Eulerian-Lagrangian (CEL) technique was used to investigate the dynamic behaviors of granular material, including the collapse of a granular column and the interaction between granular flow and a rigid barrier. The CEL technique, combining Eulerian and Lagrangian algorithms, is capable of overcoming mesh distortions of conventional finite element approaches. By validating well-established experiments, the development of progressive failure in the granular column can be accurately simulated using the equations of state (EOS) and Bingham plastic constitutive models, and the granular flow impact force on the rigid barrier based on the small-scale CEL model shows good agreement with the data measured in flume tests. The impact force simulated by the CEL technique was compared with the predictions of empirical hydrostatic and hydrodynamic models, which are the approaches generally used to estimate the granular flow impact force in engineering practice. In addition, a normalized parameter S Velocity was proposed to obtain a representative velocity and height of the granular flow from the CEL analysis to improve the accuracy of empirical approaches. The proposed parameter could benefit the in-situ monitoring of potential granular flow disasters and demonstrates the applicability of the CEL technique in practical engineering.